PELESTARIAN BUDAYA TENUN IKAT DAYAK MELALUI KADERISASI KAUM MUDA DI KABUPATEN SINTANG - Paulus, Paulus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
Abstract : Tenun Ikat, as an important cultural heritage of the Dayak community in Sintang District, West Kalimantan, reflects the cultural and philosophical identity of the local community. However, the growth of globalization and the lack of interest of younger generations in the bonding culture put the art of tenun a barrier to its preservation. The study emphasizes the importance of young people's charisma in preserving Sintang's tenun ikat. This kaderization includes education and training programmes, cultural promotion campaigns, and economic empowerment through the formation of co-operatives or joint venture groups. The educational programmes may include workshops with senior craftsmen which can be facilitated by the Sintang District Government. Promotions can use social media and cultural activities to increase young people's appreciation of their heritage. To maintain the relevance of tenun ikat in the contemporary market, young artisans acquire business and marketing skills through economic empowerment. Hopefully through this effort, the younger generation will be the keepers of tradition and also the innovators who can cultivate and bring the bandage to the global stage. In an era of globalization and modernization, the kaderisation of young people is a strategic spearhead for ensuring the sustainability of weaving and strengthening cultural identities. Keyword : preservation, culture, Tenun Ikat